Eco-Friendly Biomaterial Sticker: Redefining Anti-Radiation Solutions: Stiker Biomaterial Ramah Lingkungan: Mendefinisikan Ulang Solusi Anti-Radiasi - Asana, Mahila; Chinta, Tenri Ayuni Ratna Ade; Islamay, Febriana Nur; Nisa, Khairun; Sandi, Kurnia; Setiawati, Indah (Indonesian Journal of Innovation Studies, 2023)
This study presents an innovative sticker product crafted from environmentally sustainable biomaterials, designed to mitigate radiation exposure from electronic devices while enhancing the aesthetic appeal with the distinguished Banyumas batik motif. To ascertain market viability and effective consumer reception, a comprehensive segmentation analysis was conducted on a sample of 99 smartphone and laptop users. Employing cluster analysis, our findings reveal a strong consensus regarding the product's attributes, affirming its potential as a sustainable and effective anti-radiation solution. Moreover, this research underscores that customer preferences and values play a pivotal role in driving product innovation, alongside practical attributes and material performance. These insights have significant implications for product development and marketing strategies in the burgeoning field of anti-radiation technology. Highlight: Innovative Eco-Friendly Solution: This study introduces a novel sticker product made from sustainable biomaterials, offering a dual benefit of reducing radiation exposure from electronic devices and enhancing visual aesthetics with Banyumas batik design. Targeted Market Analysis: Through comprehensive segmentation and cluster analysis on 99 smartphone and laptop users, the research confirms a widespread consensus on the product's attributes, indicating its potential as an effective and eco-conscious anti-radiation solution. Customer-Centric Innovation: The study underscores the pivotal role of customer preferences and values in shaping product innovation, emphasizing that practical attributes and material performance alone are insufficient drivers. This insight holds significant implications for future product development and marketing strategies in the evolving anti-radiation technology landscape. Keyword: Biomaterial Sticker, Radiation Exposure Mitigation, Market Segmentation, Consumer Preferences, Product Innovation